Support Group Therapy untuk Menurunkan Kecemasan pada Care Giver Odgj di Desa Srigading - Wiwik Lestari; Triantoro Safaria (Psyche 165 Journal, 2021)
The purpose of this study group was to see the effect of group therapy in reducing cholesterol in ODGJ care givers. There were 6 participants in the group therapy which was a recommendation from the soul cadres of Srigading village. This therapy is carried out in a form analysis using a combination of qualitative and quantitative methods, with a psychodynamic-oriented approach. Group participants are drawn based on the same problem, namely the conclusion. In carrying out the obligations of the ODGJ giver, he is also a direct member of the family who also feels and feels uncomfortable while accompanying ODGJ. The results show that seen from statistical data there is a decrease in the level of attention of the giver after being given group therapy support. The results of the qualitative data also showed a decrease which was known through individual interviews after being given group therapy support